Competitive sorption of Cu(II) and Ni(II) ions from aqueous solutions: Kinetics, thermodynamics and desorption studies - Kapur M.; Mondal M.K. (My University, 2025)
Extensive study has been done in the context of single metal adsorption from aqueous solutions but the present study approaches the simultaneous sorption of metal ions. Aim of the present work is to characterize the coal dust for its ability to remove Cu(II) and Ni(II) from aqueous solutions. Variation of the working parameters viz., pH, contact time, adsorbent dose, metal ion concentrations, temperature were done in a range to optimize ideal conditions for the adsorption of ions from a binary metal solution containing Cu(II) and Ni(II) in a batch mode. Adsorption was found to be exothermic and the parameter estimation viz. δ. G°, δ. H°, δ. S° showed it to be thermodynamically favorable. Second order kinetics was fitted well for bi-component adsorption and Langmuir isotherm strongly supported the mechanism. Co-existence of the ions affected the adsorption capacity and showed antagonistic manner in comparison to the single metal. Desorption experiments showed that the coal dust can be used effectively upto three cycles and proper disposal has also been mentioned. © 2014 Taiwan Institute of Chemical Engineers.